Implementasi Program Keagamaan dalam Upaya Penguatan Karakter Religius Siswa di SMA Negeri 8 Surakarta - Aini Nur Mardiyah; Mohammad Zakki Azani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe and analyze the implementation of religious programs in strengthening students' religious character at SMA Negeri 8 Surakarta, along with the supporting factors, inhibiting factors, and efforts to overcome these obstacles. This study used a descriptive qualitative method with a case study approach. The primary data sources involved interviews and observations with the Vice Principal of Student Affairs, Islamic Education (PAI) teachers, and members of the Islamic student organization (Rohis), while secondary data were gathered through school document reviews. Data validity was tested using source and technique triangulation. The results showed that: (1) Program planning is carried out collaboratively involving cross-sectoral parties since the beginning of the new academic year based on the school's vision and mission. (2) The implementation of religious programs includes daily, weekly, and annual activities such as mass prayer, Religious Friday, Quranic literacy (BTA), Quranic recitation (Tadarus), congregational prayers, short Islamic boarding school courses (Pesantren Kilat), and Islamic holidays commemoration (PHBI). (3) Evaluation is conducted periodically through observations of students' independent worship behavior, teacher meeting reflections, and Ramadan activity logbooks. (4) Supporting factors include stakeholder commitment, strict school policies, active involvement of Rohis administrators, and supporting infrastructure. Meanwhile, inhibiting factors consist of fluctuations in students' internal motivation, limited mosque capacity, and a decline in the commitment of some Rohis administrators. These obstacles are addressed through strict punishments, innovative and interactive youth event concepts, rotational worship schedules, and optimized supervision by student organizations (PKS and MPK).